Effective use of angular momentum for rotations about the longitudinal axis - examples of quadruple jumps in figure skating - Knoll, Ka.; Hildebrand, F. (ISBS Proceedings Archive (Michigan), 2019)
Quadruple jumps (QJ) have conquered the competitions in figure skating. In men's competitions three or four different QJ is standard for top skaters. The key task of the study with 17 excellently executed QJ was to investigate the influence of the angle between the principal axis of inertia (PAI) and the vector of the angular momentum (AM) on the effective use of the angular momentum for a high angular velocity in the flight. The smallest possible angle between PAI and AM results in the most effective use of the angular momentum and a stable axis of rotation. It is of great interest for sports practice to find out which options can compensate larger angles between PAI and AM. The study shows that QJ can excellently performed even with an angle of 20 to 30 degrees between the PAI and AM. In this case, a larger angular momentum and a longer flight time are required.